Correlation study of BDNF/TrkB/CREB, violence, and cognitive function in first-episode drug-naive schizophrenia patients - Jiang, Tiankai; Li, Zhipeng; Yu, Tao; Zhou, Xudong; Jiang, Tiantian; Liang, Yuhang; Yu, Chen; Zhu, Min; Wu, Wenyu (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia (SCZ) is a complex mental disorder affecting thought processes, perceptions, and emotional regulation.MethodsThis study investigated the relationship between brain-derived neurotrophic factor (BDNF), tropomyosin receptor kinase B (TrkB), and cAMP response element-binding protein (CREB) expression with violence risk and cognitive function in first-episode, drug-naive SCZ patients. We recruited 62 SCZ patients and 62 healthy controls from the Affiliated Mental Health Center of Kunming Medical University. Sociodemographic data and psychopathological measures were collected. qRT-PCR and Western blotting assessed BDNF, TrkB, and CREB expression. Cognitive function and violence risk were evaluated using the Positive and Negative Syndrome Scale (PANSS), History of Violence, Clinical, Risk Assessment Scale (HCR-20), Modified Wisconsin Card Sorting Test (M-WCST), and Wechsler Memory Scale (WMS).ResultsCorrelation and regression analyses explored relationships between signaling factors and clinical measures. SCZ patients exhibited significantly lower BDNF, TrkB, and CREB levels than controls, higher HCR-20 scores, and impaired cognitive performance. BDNF negatively correlated with HCR-20 scores and positively with nonpreservative errors. CREB positively correlated with memory quotient. Multivariate linear regression suggested CREB plays a crucial role in both violent behavior and cognitive function in SCZ patients. Principal component analysis (PCA) combined highly correlated P_score, N_score, and PANSS_total into one principal component PC1, with logistic regression identifying PC1 as an associated factor for violence. A model incorporating BDNF, TrkB, and CREB predicted SCZ with an area under the ROC curve of 0.733.DiscussionOur findings suggest CREB plays a key role in SCZ-related violence and cognition, while BDNF, TrkB, and CREB may serve as predictive markers and potential therapeutic targets.